Increase of stimulating influence of technique intended for evaluation of activity efficiency of Doctors of science and Professors aimed at training of the University staff and elaboration of qualitative scientific materials - Mokin, B. I.; Mokina, Yu. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The technique aimed at evaluation of activity efficiency of Doctors of science and Professors in training of scientific and teaching staff and elaboration of qualitative scientific materials has been improved. Approbation data of the given methodology in VNTU is offered.